ANALISIS KESULITAN GURU DALAM PEMBUATAN RENCANA PELAKSANAAN PEMBELAJARAN KURIKULUM 2013 GUGUS 1 KECAMATAN GERUNG - Vivin Wulantari; Ida Ermiana; Itsna Oktaviyanti (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
This research aims to describe the difficulty of teachers in making the 2013 Curriculum Implementation Plan (RPP) in Group 1, Gerung District. This research is a qualitative descriptive study. Informants were selected by purposive sampling technique. Data obtained through the results of a questionnaire, structured interviews, observation and documentation. Based on the results of this study, it shows that teachers still have difficulties in making the RPP Curriculum components in 2013. There are several notes obtained from the results of the analysis, namely: learning strategies (24.64%), time allocation (27.05%), basic competence (13,52%), indicators of competency achievement (62.32%), learning objectives (53.62%), learning materials (9.06%), learning approaches and models (54.59%), learning media (59.42%) ), Learning steps (62.32%), learning resources (20.29%) and assessments (46.38%). Based on the results of the research conducted, it can be concluded that the teacher has difficulty making learning steps, learning approaches and models, competency achievement indicators, learning objectives, learning media and assessment.